The Duty to Consult the Sámi in Norwegian Law - Øyvind Ravna (Arctic Review on Law and Politics, 2020)
This article deals with the duty to consult indigenous peoples and the obligation to involve these peoples in decision-making processes in matters that concern them. After a general review of international legislation and obligations, particularly the ILO Convention no. 169 on Indigenous and Tribal Peoples, the article focuses on how these obligations are implemented towards the indigenous Sámi in Norwegian law. Here, the consultation agreement from 2005 and the Sámi Rights Committee’s 2007 draft are still central. The review includes an analysis of the extent to which these duties meet international law requirements, and a deliberation on the concept of free, prior and informed consent.